Effectiveness Of Multifaceted Care Bundle Approach To Reduce Device Associated Infection (Dai) In Critical Care Unit (Ccu) In A Multi Specialty Hospital, Mangaluru (Journal of Pharmaceutical Negative Results, 2022)
Device-associated infections (DAI) can cause major medical and economic sequelae. Multifaceted care bundle is considered as an important part of routine nursing activity, not only as a measures DAI prevention, but as a crucial treatment with a profound effect on the patients general health.ObjectivesTo measure the Device associated infection status of CLABSI, CAUTI, and VAP in pre implementation phase according to HAI surveillance guidelines.To determine the compliance status of health care workers of care bundles on prevention and care of device associated infections in CCU in Phase III.To evaluate the effectiveness of multifaceted care bundle approach on device associated infections status of CLABSI, CAUTI, & VAP in CCUTo find the risk of DAI in patients in the Post implementation phase (Phase III)Methods: An experimental approach was adopted to study the effectiveness of multifaceted care bundle approach to reduce device associated infection (DAI) in critical care unit (CCU) in a multispecialty hospital, Mangaluru. Universal sampling technique was adopted to select the 472 sample retrospectively (MRD and HIC records of DAI patients of critically care units) and 409 samples as prospectively (current critically ill patients) then implementation of bundle was done and post implementation evaluation done.Results: While comparing pre and post implementation phases, it is found that there was reduction in CAUTI rate /1000 catheter days and CLASBI rate/1000 central line days from Phase I to phase III and increase in VAP rate /1000 ventilator days from Phase I to phase III. Increase in device utilization ratio of CAUTI and CLASBI from Phase I to III and reduction in VAP device utilization ratio from Phase I to III, also observed that during pre-implementation phase, the VAP rate, CLABSI rate and CAUTI rate for all the ICU’s taken together were 134.37/1000 ventilator days, 412/1000 central line days, and 332.92/1000 urinary catheter days, respectively. However, during the post implementation the rates reduced into 133.92, 287.98, and 242 per 1000 device days respectively. There was a month wise decreasing trend of VAP rate, CLABSI rate, and CAUTI rate during the study period.In males CAUTI, CLABSI AND VAP rates were reported highest in the both Phases (I and III) and CAUTI, CLABSI and VAP difference in both Phases was not statistically significant according to age and gender (p=0.500) .Highest number of CAUTI was reported in Phase I compared to Phase III .Total number of device days were more (352) for CAUTI whereas 340 ventilator days for VAP, 292 central line days in the Phase I. While comparing both Phases significant difference was found in CAUTI (0.0017) CLASBI (0.002) and VAP (0.0016 ).Conclusion: From the findings of the study it can concluded that multifaceted care bundle significantly reduced DAIs in critically ill patients